Self-Assembly Fabrication of Hollow Mesoporous Silica@Co–Al Layered Double Hydroxide@Graphene and Application in Toxic Effluents Elimination - Jiang, Shu-Dong; Song, Lei; Zeng, Wen-Ru; Huang, Zheng-Qi; Zhan, Jing; Stec, Anna A; Hull, T. Richard; Hu, Yuan; Hu, Wei-Zhao (ACS applied materials & interfaces, 2015)
Here, we propose a self-assembly process to prepare hierarchical HM-SiO2@Co–Al LDH@graphene, with the purpose of combining their outstanding performance. Hollow mesoporous silica was first synthesized as the core, using a novel sonochemical method, followed by a controlled shell coating process and chemical reduction. As a result of the electrostatic potential difference among HM-SiO2, Co–Al LDH, and graphene oxide, the HM-SiO2 spheres were coated by Co–Al LDH and graphene. Subsequently, the HM-SiO2@Co–Al LDH@graphene spheres were introduced into an epoxy resin (EP) matrix for investigation of their toxic effluents capture and elimination effectiveness during combustion. The amount of toxic CO and volatile organic compounds from the epoxy resin decomposition significantly suppressed after incorporating the HM-SiO2@Co–Al LDH@graphene hybrids, implying a reduced toxicity.